Development of the program for sustainability of technological development of an industrial enterprise - A. E. Miller; D. O. Drozdov (Омский научный вестник: Серия "Общество. История. Современность")
The article presents the results of a study of the conceptual foundations of the sustainability of technological development in the context of import substitution. The considered methodology of sustainability determines the purpose and key tasks, organizational and economic algorithm, methodological principles of technological development. The distinctive features of the proposed methodology include: systematization of typological factors of sustainability of technological development; justification of factors influencing the sustainability of technological development. The concept under consideration clarifies the key principles of the classical theory of sustainability of development, which make it possible to explore problem areas that hinder technological development. In the context of the actual implementation of the methodology of sustainability of technological development, a methodological approach to the choice of options for assessing the program of sustainability of technological development is justified. It is advisable to implement the proposed approach on the basis of quantitative indicators formed on the basis of displaying the qualitative certainty of innovation-oriented and progressive technologies. The advantage of the proposed approach is the substantiation of the typological sequence of the formation of the structure of the program of sustainability of technological development of an industrial enterprise. The advantages of the proposed approach include the possibility of specifying the estimated indicators and their impact on the sustainability of the technological development of an industrial enterprise: 1) the achievability of a quantitative assessment of the level of losses or the amount of profitability based on the selected option of the program of sustainability of technological development of an industrial enterprise; 2) the high possibility of detecting the factors of problematic situations that cause the need for their immediate leveling; 3) the potential for the formation of a real system process of integrating innovation-oriented and progressive technologies into the formation of the production and technological potential of industrial enterprises; 4) creating conditions for the development of optimal program and scenario options for the sustainability of technological development.